2010
DOI: 10.1016/j.jpainsymman.2009.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Discussing End-of-Life Care Goals with Inpatients Using a Structured, Conversational Approach: The Go Wish Card Game

Abstract: Establishing goals of care is important in advance care planning. However, such discussions require a significant time investment on the part of trained personnel and may be overwhelming for the patient. The Go Wish card game was designed to allow patients to consider the importance of common issues at the end of life in a nonconfrontational setting. By sorting through their values in private, patients may present to their provider ready to have a focused conversation about end-of-life care. We evaluated the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 19 publications
1
44
2
10
Order By: Relevance
“…Using simple tools, Lankarani‐Fard et al (2010) found that a card‐sorting game can be effective in identifying individuals’ values and priorities for end‐of‐life care.…”
Section: Resultsmentioning
confidence: 99%
“…Using simple tools, Lankarani‐Fard et al (2010) found that a card‐sorting game can be effective in identifying individuals’ values and priorities for end‐of‐life care.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies elaborate on other efforts to further support patients in light of the common issues experienced during end of life scenarios in non-confrontational settings. For example, different approaches can be utilized in conjunction with the go wish card game (Lankarani-Fard et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Go Wish Card© game was a structured, conversational game to explore EOL wishes in a nonthreatening manner ( Potthoff, 2015 ). The Go Wish Card© game was previously used in inpatient and community settings ( Lankarani-Fard et al, 2010 ; Menkin, 2007 ). The game contains 36 cards, each representing items recognized as important at the EOL.…”
Section: Methodsmentioning
confidence: 99%